2020
DOI: 10.12973/eu-jer.9.2.489
|View full text |Cite
|
Sign up to set email alerts
|

Contributing Factors of Secondary Students’ Attitude towards Mathematics Contributing Factors of Attitudes towards Mathematics

Abstract: The research investigated the effect of socioeconomic status, gender, perceived parental influences, teacher affective support, classroom instruction and previous achievement on students' attitude towards mathematics. The comparison of these effects was also done between urban and rural school students. This research employed a cross-sectional quantitative design based on a structural equation modelling approach. The sample consisted of 808 students from ten secondary schools in Sabah, three of which were urba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The problem solving process requires appropriate concepts, principles and procedures in order to obtain the desired answers and is called an internal connection, connection in mathematics. The role of the teacher in learning mathematics in the classroom (Davadas & Lay, 2020;Toheri et al, 2020) and the skills of the teacher in choosing math problem solving strategies (Barham, 2020) are very important so that students are skilled in problem solving.…”
Section: Discussionmentioning
confidence: 99%
“…The problem solving process requires appropriate concepts, principles and procedures in order to obtain the desired answers and is called an internal connection, connection in mathematics. The role of the teacher in learning mathematics in the classroom (Davadas & Lay, 2020;Toheri et al, 2020) and the skills of the teacher in choosing math problem solving strategies (Barham, 2020) are very important so that students are skilled in problem solving.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies on students' attitude towards mathematics which is always translated as liking and disliking of the subject have been published (e.g., [6][7][8][9]). To some secondary school students, mathematics appears abstract, difficult to comprehend, boring and viewed with limited relationship or relevance to everyday life experiences.…”
Section: The Concept Of Students' Attitude Towards Mathematicsmentioning
confidence: 99%
“…The researchers concluded that Tanzanian students had positive attitudes towards mathematics, and the reasons for these attitudes were: (1) feeling joy when learning mathematics, (2) academic competence of the student, (3) teaching methods, (4) classroom educational environment, (5) availability of scientific means in the school, and (6) tests results. Several studies indicate the influence of other factors such as colleagues and friends (He, 2007;Yang, 2013), family and parents (Davadas & Lay, 2020), school (Laguador & Dotong, 2020;Yang, 2013), teachers' personal characteristics (Al Shabibi, Al Mantheri, & Al Rashdi, 2019;Blazar & Kraft, 2017;Sakiz, Pape, & Hoy, 2012), teachers' knowledge of content (Simmers, 2011), language (Mazana, Montero, & Casmir, 2019), and how mathematics relates to daily life (Yılmaz, Altun, & Olkun, 2010).…”
Section: Reasons For Students' Attitudes Toward Mathematicsmentioning
confidence: 99%